Immunogenicity of two doses of BNT162b2 and mRNA‐1273 vaccines for solid cancer patients on treatment with or without a previous SARS‐CoV‐2 infection. Issue 4 (28th September 2022) - La Verde, Nicla; Riva, Agostino; Cona, Maria Silvia; Gabrieli, Arianna; Cattaneo, Monica; Fasola, Cinzia; Lipari, Giuseppe; De Stradis, Claudia; Favorito, Valentina; Lombardi Stocchetti, Benedetta; Chizzoniti, Davide; Covizzi, Alice; et al.
Abstract: Previous studies on the immunogenicity of SARS‐CoV‐2 mRNA vaccines showed a reduced seroconversion in cancer patients. The aim of our study is to evaluate the immunogenicity of two doses of mRNA vaccines in solid cancer patients with or without a previous exposure to the virus. This is a single‐institution, prospective, nonrandomized study. Patients in active treatment and a control cohort of healthy people received two doses of BNT162b2 (Comirnaty, BioNTech/Pfizer, The United States) or mRNA‐1273 (Spikevax, Moderna). Vaccine was administered before starting anticancer therapy or on the first day of the treatment cycle. SARS‐CoV‐2 antibody levels against S1, RBD (to evaluate vaccine response) and N proteins (to evaluate previous infection) were measured in plasma before the first dose and 30 days after the second one. From January to June 2021, 195 consecutive cancer patients and 20 healthy controls were enrolled. Thirty‐one cancer patients had a previous exposure to SARS‐CoV‐2. Cancer patients previously exposed to the virus had significantly higher median levels of anti‐S1 and anti‐RBD IgG, compared to healthy controls ( P = .0349) and to cancer patients without a previous infection ( P < .001). Vaccine type (anti‐S1: P < .0001; anti‐RBD: P = .0045), comorbidities (anti‐S1: P = .0274; anti‐RBD: P = .0048) and the use of G‐CSF (anti‐S1: P = .0151) negatively affected the antibody response. Conversely, previous exposure to SARS‐CoV‐2 significantly enhanced the response to vaccination (anti‐S1: P < .0001; anti‐RBD: P = .0026). Vaccine immunogenicity in cancer patients with a previous exposure to SARS‐CoV‐2 seems comparable to that of healthy subjects. On the other hand, clinical variables of immune frailty negatively affect humoral immune response to vaccination. Abstract : What's new? Although mRNA‐based vaccines that protect against infection with SARS‐CoV2, the causative virus of COVID‐19, are highly immunogenic in healthy individuals, the extent to which they provoke immune responses in cancer patients is less certain. Here, the immunogenicity of two doses of either of two SARS‐CoV2 mRNA vaccines was investigated in cancer patients with solid tumors. Patients previously exposed to SARS‐CoV2 exhibited strong immune responses to vaccination, similar to responses in healthy controls. Responses were more muted among patients with no prior SARS‐CoV2 exposure. Antibody responses to vaccination also were negatively impacted by comorbidities, use of G‐CSF and vaccine type.